Using neuromuscular electrical stimulation in conjunction with ultrasound imaging technique to investigate lumbar multifidus muscle activation deficit - Wattananon, Peemongkon; Sungnak, Panakorn; Songjaroen, Sranya; Kantha, Phunsuk; Hsu, Wei-Li; Wang, Hsing-Kuo (Musculoskeletal science & practice, 2020)
Lumbar multifidus muscle (LM) activation deficit has been proposed as a potential underlying mechanism responsible for recurrence episode of low back pain (LBP). The quantification of voluntary LM activation can provide a better understanding of the role of muscle activation deficit in LBP. The objective of this technical report is to propose a new approach using neuromuscular electrical stimulation (NMES) in combination with the ultrasound imaging technique (USI) to investigate the ability of individual to voluntarily activate the LM. We recruited ten participants with a recurrent LBP (rLBP) and twelve participants with no history of LBP (NoLBP). Theoretically, the superimposition of NMES on the LM during maximum voluntary isometric contraction (MVIC) should activate all motor units available in the LM. The percentage of LM activation (%LM) can be calculated by the changes of LM thickness during MVIC, divided by the changes of LM thickness during the combination of MVIC and NMES. This %LM was used to compare between groups. The individuals with rLBP had significantly lower %LM (p < 0.05) compared with the NoLBP counterpart (%LM = 72.4 and 92.9, respectively). Results demonstrate that this new approach can potentially differentiate %LM among individuals with rLBP and NoLBP. This new approach can be potentially used to 1) determine the extent of LM activation deficit, 2) identify the existence of muscle activation deficit in the LM, and 3) objectively measure the effect of the intervention designed to address the LM activation deficit. •Electrical stimulation with ultrasound imaging can measure multifidus activation.•The % multifidus activation between individuals with and without recurrent LBP.•New approach can investigate the extent of multifidus muscle activation deficit.